Strategi Kepala Sekolah dalam Meningkatkan Partisipasi Masyarakat di Sekolah Menengah Atas Swasta - Yunita, Nurma (Center for Religious Studies and Social Empowerment Foundation, 2023)
This article wants to discuss the Principal's Strategy in Increasing Community Participation. The focus of the study in this article is how is the Principal's Strategy in Increasing Community Participation in Islamic Senior High Schools? This research is a qualitative research with a phenomenological approach. The research findings show that the process carried out by the school in increasing community participation has been carried out in various forms, although it has not been maximized. What has been done by the principal is using the strategy of establishing effective communication between the principal and the surrounding community, identifying with key people in the community, inviting parents and community leaders to school activities and collaborating with relevant agencies. As well as there are also obstacles faced by a lack of time to socialize with parents, some parents leave education to their children, do not provide support to them, are not motivated to improve education determined by the school, the influence of the child's environment in getting along, lack of awareness of children in discipline. Artikel ini hendak membahas tentang Strategi Kepala Sekolah dalam Meningkatkan Partisipasi Masyarakat. Fokus kajian dalam artikel ini adalah bagaimana Strategi Kepala Sekolah dalam Meningkatkan Partisipasi Masyarakat di Sekolah Menengah Atas Islam ? Penelitian ini merupakan penelitian kualitatif dengan pendekatan fenomenologi. Temuan penelitian menunjukkan bahwa proses yang dilakukan pihak sekolah dalam meningkatkan partisipasi masyarakat telah dilakukan dalam berbagai bentuk proses walau belum maksimal. Hal yang telah dilakukan oleh kepala sekolah menggunakan strategi menjalin komunikasi yang efektif antara kepala sekolah dengan masyarakat sekitar, melakukan identifikasi dengan orang-orang kunci dikalangan masyarakat, mengundang orang tua murid dan tokoh masyarakat dalam kegiatan sekolah dan menjalin kerjasama dengan instansi terkait. Serta terdapat pula kendala yang dihadapi kurangnya waktu untuk bersosialisi kepada orang tua, sebagian orang tua menyerahkan tentang pendidikan kepada anak mereka tidak memberikan dukungan kepada mereka, tidak termotivasi dalam mengkatkan pendidikan yang ditentukan oleh sekolah, adanya pengaruh lingkungan anak dalam bergaul, kurangnya kesadaran anak dalam kedisiplinan.